Análisis de la oferta turística cultural en Ventanas: Identificación de atractivos y necesidades de desarrollo - Cellan Alarcón, Anthony Fabricio (2025)
This case study is directed towards the analysis of the cultural tourism supply in the Ventanas canton and the identification of attractions and development needs to implement the management and promotion of tourism in the locality. A quantitative methodology is used to analyze the tourism supply and demand in the Ventanas canton and to identify the attractions of the locality to implement strategies for tourism development in the region. The starting point is a descriptive design based on the bibliographic section presented in the conceptual framework and the fulfillment of the proposed objectives through the application of a survey to a convenience sample of 50 people, including residents and tourists who visit the Ventanas canton. The results obtained from the applied surveys allow the establishment of conclusions and recommendations that, in general, establish that due to the cultural and natural attractiveness of the Ventanas canton, the need to develop an inventory of cultural tourism attractions and the development of tourism promotion campaigns to attract visitors to the locality is evident.